2023
DOI: 10.3390/su15075895
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation Management Cost and Maintenance Implications of Different Ground Covers at Utility-Scale Solar Sites

Abstract: Utility-scale solar photovoltaics (PV) is the largest and fastest-growing sector of the solar energy market, and plays an important role in ensuring that state and local jurisdictions can meet renewable energy targets. Potential adverse environmental impacts of utility-scale solar PV are well-documented, and the effects of diverse mitigation and dual land use strategies under the banner of 'low-impact solar' are justly receiving more attention; this article seeks to contribute to improving understanding of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…For such seeding, there has unfortunately (until recently) seemed to be little incentive to spend more capital than on the absolute cheapest grass species, or even gravel, if permitted by local authorities. (McCall et al, 2023).…”
Section: Power Densities On Locopvmentioning
confidence: 99%
See 2 more Smart Citations
“…For such seeding, there has unfortunately (until recently) seemed to be little incentive to spend more capital than on the absolute cheapest grass species, or even gravel, if permitted by local authorities. (McCall et al, 2023).…”
Section: Power Densities On Locopvmentioning
confidence: 99%
“…Studies and experiences have shown that such techniques as planting native groundcover species (though often a higher initial cost than turfgrass or gravel) can decrease long-term O&M expenditures on vegetation and soil erosion management (McCall et al, 2023). Some of these native species that show long-term stability are flowering plants, which have been shown to boost pollinator populations, leading to the coining of the term "pollinator-friendly solar" in the US.…”
Section: Lowest-cost Ecovoltaicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Establishing pollinator habitat at solar sites has been referred to as both agrivoltaics and ecovoltaics in current literature, but agrivoltaics can include other land uses such as animal grazing and crop production [9,10]. Pollinator habitat at solar facilities may also directly contribute to agriculture production through honey production from apiaries located on site [11].…”
Section: Introductionmentioning
confidence: 99%
“…In agricultural settings, crop production and solar PV can be laterally integrated (agrisolar colocation) 19 , and/or directly share land and photons via vertical integration (agrivoltaic colocation) 20,21 .Effective agrivoltaic management can improve agricultural yield, microclimate regulation, soil moisture retention, nutrient cycling 12,[22][23][24][25][26] , and farmer profitability 24,27,28 , while reducing public opposition 29,30 . Aside from installation and management costs concerns [31][32][33] , agrivoltaics have few net-negative consequences 12,21,[34][35][36] . However, techno-economic and political challenges remain for broad deployment of this practice 35,[37][38][39] .…”
mentioning
confidence: 99%